2010
DOI: 10.1002/app.33037
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nano/micro‐calcium carbonate particles/polypropylene composites

Abstract: A new kind of polypropylene (PP)/CaCO 3 composites was prepared on a twin screw extruder with the nanoparticle content of 5 wt % and the 2500 mesh microparticle content of 15 wt %. The mechanical property of four different samples [pure PP (1), PP filled with 15 wt % microCaCO 3 particle composites (2), PP filled with 5 wt % nanoCaCO 3 particle composites (3) and PP filled with micro/nano-CaCO 3 complex size particle composites (4)] was investigated through tensile tests, notched Izod impact tests and SEM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…A statistical analysis and a 2 2 factorial experimental design were employed to evaluate the effects of the rheological performance of polypropylene/calcium carbonate composites (Fig. 12) [46]. From this analysis, we observed that the addition of lower content of filler with lower particle size leads to decreased composite viscosity due to better dispersion of the filler in the polymer matrix.…”
Section: Calcite Filled Polypropylenementioning
confidence: 99%
“…A statistical analysis and a 2 2 factorial experimental design were employed to evaluate the effects of the rheological performance of polypropylene/calcium carbonate composites (Fig. 12) [46]. From this analysis, we observed that the addition of lower content of filler with lower particle size leads to decreased composite viscosity due to better dispersion of the filler in the polymer matrix.…”
Section: Calcite Filled Polypropylenementioning
confidence: 99%
“…Currey et al [110] reported that the fracture strength in bending varied between 56 and 116 MPa. Jackson et al [111] investigated the nacre from Pinctada shell and reported a Young's modulus of approximately 70 composite, as compared with the normal use of inorganic fillers such as calcium carbonate and talc [112][113][114][115]. Li et al [116][117][118][119][120] …”
Section: Fillersmentioning
confidence: 99%
“…Recently, it was reported that PP could be reinforced and toughened at the same time by the addition of surface‐modified CaCO 3 nanoparticles. Zhang et al . prepared sodium stearate‐treated nano‐CaCO 3 with average particle size of 36 nm and introduced it into PP at 5 wt % filler content.…”
Section: Introductionmentioning
confidence: 99%